2010
DOI: 10.4028/www.scientific.net/kem.438.195
|View full text |Cite
|
Sign up to set email alerts
|

Modified DLC-Coated Guide Pads for BTA Deep Hole Drilling Tools

Abstract: The BTA (Boring and Trepanning Association) deep hole drilling process is commonly used to machine boreholes with a large drilling depth-to-diameter ratio (l/D) and outstanding workpiece quality. The asymmetric tool design leads to a nonzero radial component of the cutting force and the passive force, which are conducted to the borehole wall by so-called guide pads. These guide pads smooth the borehole wall by a forming process and improve the surface quality. Processes, that machine materials with a high adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Different studies showed, that it is possible to adjust the damping of the drilling process by adjusting the land width [22][23][24]. Previous investigations have insufficiently dealt with the influence of the land width on the vibration of twist drills.…”
Section: Research Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Different studies showed, that it is possible to adjust the damping of the drilling process by adjusting the land width [22][23][24]. Previous investigations have insufficiently dealt with the influence of the land width on the vibration of twist drills.…”
Section: Research Objectivementioning
confidence: 99%
“…It can be deduced that damping in form of friction at the main cutting edges as a result of wear does not lead to avoid lateral vibrations. Biermann et al [23,24] investigated the damping during Boring and Trepanning Association (BTA) drilling, in which the authors varied the geometry of the guide pads on the tool, including the coating. The results led to a reduction in abrasive wear and to improve the surface of the bore wall.…”
Section: Introductionmentioning
confidence: 99%
“…During the machining process, high mechanical loads stress the guide pads, which lead to an extensive wear of these components [3]. Depending on the materials to be machined, such as austenitic steels, these loads increase and exceed the initial state multiple [4]. These steel grades in particular cause high abrasive and adhesive tool wear [5].…”
Section: Introductionmentioning
confidence: 99%
“…These steel grades in particular cause high abrasive and adhesive tool wear [5]. Previous research at the Institute of Machining Technology has already focused on the wear of guide pads in single tube system (STS) deep hole drilling of austenitic steels [4,6]. Special attention was paid to the shape of diamond-like carbon (DLC)-coated guide pads, on tool wear behaviour and on quality of the drilled bore holes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation